NEEDS ANALYSIS FOR DEVELOPING A BOARD GAME TO IMPROVE SPEAKING SKILLS IN THIRD GRADE ELEMENTARY STUDENTS - Nurlaela; Gusti Yarmi; Cecep Kustandi (SOSIOEDUKASI, 2025)
This research aims to analyze the needs for developing a board game as a learning medium to to enhance the speaking skills of third-grade elementary school students. Speaking is a crucial language skill that supports communication, confidence, and idea expression. However, many students still struggle to speak fluently and confidently, especially especially in storytelling. A fun and interactive learning medium is needed to address this issue, in line with students' cognitive development. This qualitative descriptive study involved interviews, observations, and questionnaires with teachers and students in a public elementary school. The findings reveal a lack of varied and engaging media for speaking activities. Students show strong interest in game-based learning, especially when it includes local cultural content and progressive challenge levels. The results indicate that a well-designed board game can effectively encourage student participation and improve their speaking abilities. This analysis will serve as the foundation for developing a board game prototype for third grade learners’ needs.